Consumption of animal-based and processed food associated with cardiovascular risk factors and subclinical atherosclerosis biomarkers in men - Acosta-Navarro, Júlio César; Oki, Adriana Midori; Antoniazzi, Luiza; Bonfim, Maria Aparecida Carlos; Hong, Valeria; De Almeida Gaspar, Maria Cristina; Sandrim, Valeria Cristina [UNESP]; Nogueira, Adriana (FapUNIFESP (SciELO), 2019)
OBJECTIVE: To evaluate the frequency of food consumption in apparently healthy men and their association with cardiovascular risk factors and biomarkers of subclinical atherosclerosis. METHODS: In this observational study, 88 men had their food standard obtained through the food frequency questionnaire (FFQ). Associations of dietary patterns with cardiovascular risk factors, such as anthropometric data, laboratory and clinical evaluations, carotid-femoral arterial stiffness (IMT) and pulse wave velocity were evaluated. RESULTS: The highest values were observed, for most of the risk factors evaluated, with the highest frequency of weekly consumption of dairy products, meats, sweets, fats, cold meats, sodas, milk and white chocolate; and lower frequency of weekly consumption of fruits, cereals, vegetables, legumes, oilseeds, and soy. There was no significant difference for coffee and dark chocolate CONCLUSIONS: A diet with high consumption of animal products has a higher correlation with cardiovascular risk factors; the opposite is true for the consumption of plant-based food, associated with the profile of more favorable biomarkers for cardiovascular health and better biochemical and structural parameters.
Keywords: Atherosclerosis; Food Consumption; Pulse Wave Analysis; Vascular Stiffness